Scaling of bite force corresponds with ontogenetic niche shifts in coastal elasmobranchs - Cullen, Joshua A.; Marshall, Christopher D. (Frontiers in Marine Science, 2024)
Introduction Predators, such as sharks, play important ecological roles in coastal ecosystems when abundant and these roles change over ontogeny. However, these shifts in ecological role are often not evaluated in light of feeding performance. Bite force is an ecologically relevant metric of feeding performance that has been associated with a species’ foraging niche, which may serve as a key factor that constrains prey selection both within and among sympatric species. Methods This study applies an interdisciplinary approach to discern the ecomechanical relationships of sympatric bull (Carcharhinus leucas), blacktip (Carcharhinus limbatus), and bonnethead sharks (Sphyrna tiburo) using feeding biomechanics and bulk stable isotopes (δ13C, δ15N). We sought to (1) estimate theoretical bite force and scaling patterns over ontogeny of each species, (2) quantify niche breadth and overlap among species, and (3) characterize the relationship between ecological niche shifts and changes in bite force over ontogeny. Results Importantly, we found that smaller conspecifics exhibited positive allometric scaling of bite force, whereas larger conspecifics exhibited isometric scaling. Associations between bite force and ontogenetic niche shifts in habitat and diet were found in bull and bonnethead sharks, but not in blacktip sharks. Additionally, isotopic niche breadth was greatest in generalist bull sharks, followed by specialist bonnethead and blacktip sharks. Discussion These findings highlight animal performance measures as critical drivers ofecological relationships both within and among species. Size-based differences in bite force scaling should be considered when evaluating feeding performance in other taxa, which may be an important determinant of ontogenetic dietary shifts.